Sexual risk behaviours and correlates of condom use with casual sex partners among drug users in Jiangsu, China. (3rd September 2019) - Zhao, Qun; Mao, Yuchen; Sun, Mengqi; Li, Xiaoming
Abstract: The study aimed to explore sexual risk behaviours and the correlates of condom use with casual sex partners among drug users in China. Data were collected from 901 eligible drug users (504 men and 397 women) from 2014 to 2015 in Jiangsu, China. Methamphetamine was the most used drug (91.8%) among the participants. The proportion reporting consistent condom use was 4.1 and 11.9% with steady and casual sex partners, respectively. Compared to women, men were more likely to have had their first sex at age ≤16 years (40.3 versus 25.6%), had both steady and casual sex partners (68.0 versus 28.9%), had one night stand partners (54.6 versus 17.4%), had sex under the influence of drugs often (29.8 versus 3.6%). Multiple logistic regressions indicated that inconsistent condom use with casual sex partners was associated with older age, having drug use friends as casual sex partners, while having always used condoms was associated with having never had sex under the influence of drugs, having sought casual sex less frequently, and using condoms at first sex. The findings highlight the need for future gender-specific efforts toward tailoring prevention and treatment programmes to reduce sexual risk behaviours among drug users in China.